Interaction Questions Efforts to Preserve Maluku Musical Instruments as Traditional Knowledge in the Protection of Intellectual Property Rights: Interaksi Menyoal Upaya Pelestarian Alat Musik Khas Maluku Sebagai Pengetahuan Tradisional Dalam Perlindungan Hak Kekayan Intelektual - Balik, Agustina; Tjoanda, Merry; Panjaitan, Wijaya Natalia; Lenggono, Roy Prabowo (AIWADTHU: Jurnal Pengabdian Hukum, 2026)
Introduction: Indonesia has an abundant wealth of arts and culture, including traditional Maluku musical instruments such as the Tifa Totobuang and the Ukulele Kembar. This musical instrument is an important heritage of traditional knowledge, but it is vulnerable to copyright claims by foreign parties and has not received adequate Intellectual Property Rights (IPR) legal protection. Performing arts actors and musical instrument craftsmen in Ambon City have a high initiative to preserve their works, but there is still a lack of understanding of the legal aspects of IPR that can provide protection. Purposes of The Devotion: This activity aims to implement the results of previous research on copyright registration as a guarantee of legal protection of Traditional Knowledge, especially typical Maluku musical instruments. In addition, this activity also aims to be a form of education and increase legal understanding in the field of IPR for Performing Arts Actors and Musical Instrument Craftsmen in Ambon City. Method of The Devotion: This community service activity uses the implementation method in the form of discussion and sharing of legal knowledge directly (person by person) with Performing Arts Actors and Musical Instrument Craftsmen in Ambon City. The stages of the activity include initial coordination, preparation of discussion materials, implementation of discussions and knowledge sharing, as well as the location of activities in the place of each artist and craftsman. Results Main Findings of the Devotion: Discussion and knowledge sharing activities revealed that Performing Arts Actors and artisans of traditional Maluku musical instruments in Ambon City have high initiative and hard work in preserving their musical instruments. However, they still lack understanding about IPR protection, how to register, and the importance of this legal aspect to prevent the use of works without rights by other parties. Through this activity, there is a desire and awareness to protect traditional musical instruments through copyright registration. This activity is expected to open up insights and increase legal understanding in the field of IPR for art actors and craftsmen.